TINDAK TUTUR ILOKUSI DALAM INTERAKSI ANTARA PEDAGANG DENGAN PEMBELI DI PASAR PANAM KECAMATAN TAMPAN KOTA PEKANBARU - Usani, Rabil Usani; ', Auzar; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research entitled The Illocutionary Speech Act in Interaction Between Traders to Buyers in the Market Panam Kecamatan Tampan Pekanbaru City. A problem that investigated in this research is kind of a speech act ilokusi contained in the interaction between traders to buyers in the market panam. This research aims to understand the type of a speech act ilokusi contained in the interaction between traders with buyers market panam d sub-district handsome pekanbaru. The research is qualitative research methods descriptive. The object of this research in the form of tuturan uttered by traders to buyers in the market panam handsome sub-district pekanbaru. Data collection techniques in this research using simak, technique record, technique and techniques logged. The result of this research shows that kind of a speech act ilokusi found was a speech act ilokusi assertive, directive, komisif, expressive, and declarative. Ilokusi assertive that found is assertive said , made known , and complain. Ilokusi directive is directive order, pleading, suggesting, asked, urge and entreat, give you, challenge, sent, invite, and ordered. Ilokusi komisif found was komisif offer, promising, ability and said. Ilokusi expressive found was expressive of saying thank you and blame. Ilokusi declarative found was declarative pointed. Research is expected can be beneficial for for an audience to deepen the science of pragmatik particularly on ilokusi a speech act. Key Words: Speech act ilokusi, assertive, directive, komisif, expressive